Synthesis of a novel hybrid nanocomposite based on copper pentacyanonitrosylferrate and octa(aminopropyl)silsesquioxane and its behavior on L-cysteine electrooxidation - de Souza Magossi, Mariana [UNESP] (2019)
In this study, a novel silsesquioxane and copper pentacyanonitrosylferrate compound was prepared starting from octa(aminopropyl)silsesquioxane (CA) following a new synthesis route. The prepared composite (ACCuN) was characterized by spectroscopic techniques, such infrared (FTIR), Scanning Electron Microscopy coupled with Energy X-Ray (SEM-EDS), Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Diffuse Reflectance UV/Vis, Electronic Paramagnetic Resonance (EPR) and cyclic voltammetry (CV). The cyclic voltammograms of the modified graphite paste electrode with ACCuN presented a redox pair with a formal potential of (Eθ') = 0.73 V (vs Ag/AgCl(sat.)) assigned to the redox couple Fe(II)(CN)5NO/Fe(III)(CN)5NO, respectively (vs Ag/AgCl(sat.); KCl 1.0 mol L−1; pH = 7.0; v = 20 mV s−1). The nanocomposite ACCuN was sensitive to L-cysteine concentrations, with a linear response from 2.0 × 10−4 to 2.0 × 10−3 mol L−1, relative standard deviation of ±2% (n = 3), and limit of detection and amperometric sensitivity of 1.25 × 10−4 mol L−1 and 10.66 mA/mol L−1, respectively.